Pengaruh Harga Emas, Harga Minyak Dunia, dan Harga Minyak Kelapa Sawit Terhadap Harga Saham Periode 2019 – 2022 - Arief Widijatmoko; Maya Puspita Anggraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted to observe the effect of gold prices, world oil prices and palm oil prices as commodity prices on the movement of stock prices in Indonesia from 2019 to 2022. The research method used is a quantitative method, using secondary data. The analysis technique used is multiple linear regression analysis technique. The research data is in the form of time series data, namely monthly data from January 2019 to December 2022. The total data is 48 for each variable. The conclusion of this study is that the price of gold has no significant effect on the Jakarta Composite Index (IHSG). World oil prices have a significant effect on the Jakarta Composite Index (IHSG). The price of Palm Oil has a significant effect on the Jakarta Composite Index (IHSG). The results of this study are to prove that gold price movements cannot be used as an indication of stock prices on the Indonesia Stock Exchange (IDX). Movements in world oil prices and palm oil prices can indicate stock prices on the Indonesia Stock Exchange (IDX). The above conditions apply for the long term.